Coupling heterostructure of thickness-controlled nickel oxidenanosheets layer and titanium dioxide nanorod arrays via immersionroute for self-powered solid-state ultraviolet photosensor applications - Mohd Yusoff, Marmeezee; Mamat, Mohamad Hafiz; Abdullah, Mardhiah; Ismail, Ahmad Syakirin; Malek, Mohd Firdaus; Zoolfakar, Ahmad Sabirin; Al Junid, Syed Abdul Mutalib; Abu Bakar, Suriani; Mohamed, Azmi; Ahmad, Mohd Khairul; Shameem Banu, Itreesh Basha; Rusop, Mohamad (Elsevier B.V., 2020)
A coupling heterostructure consisting of nickel oxide nanosheets (NNS) and titanium dioxide nanorod arrays (TNAs) was fabricated for self-powered solid-state ultraviolet (UV) photosensor applications. By controlling the thickness of the NNS layer by via varying the growth time from 1 to 5 h at a deposition temperature of 90 °C, the coupling NNS/TNAs heterojunction films were formed and their structural, optical, electrical and UV photoresponse properties were investigated. The photocurrent measured from the fabricated self-powered UV photosensor was improved by increasing the thickness of NNS from 140 to 170 nm under UV irradiation (365 nm, 750 µWcm−2) at 0 V bias. A maximum photocurrent density of 0.510 µA∙cm−2 was achieved for a sample with a NNS thickness of 170 nm and prepared with a 3 h NNS growth time. Our results showed that the fabricated NNS/TNAs heterojunction has potential applications for self-powered UV photosensors.